AIDS : A Survey Of Knowledge, Attitudes And Beliefs Of Undergraduate Students Of Delhi University - Benara S.K; Khelendra R.K; Chaudhury B.N; Bhattacharyya J; Chawla U; Bandopadhyay S; Dutta K.K (Wolters Kluwer Medknow Publications, 1992)
The 513 undergraduate students (262 male and 251 female) surveyed from five colleges of Delhi University were aware of AIDS (Acquired immunodeficiency Syndrome). They knew from different sources that sexually promiscuous people, prostitutes, intravenous drug abusers, professional blood donors and recipients of HIV infected blood were at risk for AIDS. About half of the students (57.5%) knew that AIDS was incurable and ultimately led to death. A majority of them (60-72%), also knew that AIDS could be prevented by using condoms during sexual intercourse, disposable needles during injection and avoiding sex with multiple partners. On the other hand their knowledge on non-sexual transmission was inadequate. Most of them (58%) believed that one could get AIDS by airborne, oral and kinesthetic routes, some (41%) felt that AIDS patients should not be allowed to mix in society, and 24% had an attitude of severing contact with their best friends or divorcing their spouses. The most impotent viewpoint was that 49% of them wrongly believed that AIDS could be prevented by vaccination. The need for more information on AIDS was felt by all of them.